A spatial system dynamic model for regional desertification simulation – A case study of Ordos, China. (September 2016) - Xu, Duanyang; Song, Alin; Tong, Hefeng; Ren, Hongyan; Hu, Yunfeng; Shao, Quanqin
Abstract: A spatial system dynamic (SSD) model for simulating desertification was developed by integrating climate, soil water, population, economy, pasturage, and land use. Net Primary Production (NPP) was selected as an intermediate variable to measure the impacts of driving forces and desertification grades. Ordos in China was selected to test the model. Ten scenarios were designed to simulate desertification dynamics in Ordos from 2011 to 2030. The results showed that the SSD model was reliable, and the overall accuracy of desertification degree was approximately 83%. Climate factors had relatively higher sensitivities than other parameters. Although humid climate and sustainable development strategy would reduce desertified land area and desertification degree before 2025, the rapid increase in pasturage pressure would offset this trend. Arid climate and unsustainable development strategy would accelerate desertification expansion. For local government, it is necessary to persist in the present desertification prevention policy and completely banned grazing after 2025. Highlights: A spatial system dynamic model for desertification simulation was developed. Climate, soil water, population, economy, pasturage and land use were coupled. Ten scenarios were designed to simulate desertification dynamics in Ordos, China. Some suggestions from model were given to local government to combat desertification.